2005
DOI: 10.1002/adma.200500275
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication of an Upright‐Standing Zinc Oxide Nanosheet for Use in Dye‐Sensitized Solar Cells

Abstract: Zinc oxide, an n-type semiconductor with a direct bandgap of 3.3 eV, has attracted interest from many academic and industrial researchers due to its wide array of applications in the design of chemical sensors, [1] photocatalysts, [2] phosphors, [3] and dye-sensitized solar cells. [4,5] In particular, ZnO has attracted attention as a fascinating alternative to TiO 2 in dyesensitized solar cells (DSCs) based on recent reports that demonstrated that ZnO and TiO 2 exhibit a similar electroninjection process from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
261
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(265 citation statements)
references
References 20 publications
4
261
0
Order By: Relevance
“…The electrode consisted of active material (SnO 2 ), conductivity agent (acetylene black, Alfa Aesar), and polymer binder (poly(vinylidene difluoride), 4 , which was explicitly revealed by XRD (see Supporting Information, Figure S1). This XRD result indicated that, at ambient condition, the precursor SnCl 2 mainly transformed into poorly crystallized Sn 6 4 . 52,53 However, the addition of NH 3 ·H 2 O quite favored this transition judging from the severe darkening of suspension color (from white to dark yellow-white), thus leading to higher yield of Sn 6 O 4 (OH) 4 .…”
Section: ■ Introductionmentioning
confidence: 93%
“…The electrode consisted of active material (SnO 2 ), conductivity agent (acetylene black, Alfa Aesar), and polymer binder (poly(vinylidene difluoride), 4 , which was explicitly revealed by XRD (see Supporting Information, Figure S1). This XRD result indicated that, at ambient condition, the precursor SnCl 2 mainly transformed into poorly crystallized Sn 6 4 . 52,53 However, the addition of NH 3 ·H 2 O quite favored this transition judging from the severe darkening of suspension color (from white to dark yellow-white), thus leading to higher yield of Sn 6 O 4 (OH) 4 .…”
Section: ■ Introductionmentioning
confidence: 93%
“…In this regard, studies on nanotubes [455,456], nanoparticle/nanowire composites [453,[457][458][459][460], hierarchical [199,461] structures [209,[462][463][464], and different growth parameters [465] have been shown to give several-fold increases in efficiency (Fig. 56(b)).…”
Section: Reproduced With Permissionmentioning
confidence: 99%
“…The DSC using the ZnO and Eosin Y as the dye indicated the conversion efficiency of 2%. 10) The oriented ZnO nanosheet film 15) was fabricated thorough the oriented layered hydroxide zinc carbonate nanosheet film by self-template method as shown in Fig. 3(b).…”
Section: Dsc By Self Template Methodsmentioning
confidence: 99%